Geodiversity and its implications in the conservation of biodiversity: Some case studies in central Mexico - Bravo-Cuevas, Victor Manuel; González-Rodríguez, Katia Adriana; Cabral-Perdomo, Miguel Angel; Cuevas-Cardona, Consuelo; Pulido-Silva, María Teresa (CIENCIA ergo-sum; Vol. 28 Núm. 3 (2021): CIENCIA ergo-sum (noviembre 2021-febrero 2022)DO - 10.30878/ces.v28n3a8, 2021)
Geodiversity refers to the abiotic components of the Earth, although in some cases it has been related to biodiversity in terms of conservation biology. The fossil record is one of the components of geodiversity that testifies the evolution of biota in the geological past; it has great importance when proposing strategies for the integral conservation of extant natural resources. In this regard, is that paleobiological conservation integrates relevant paleontological and ecological information that has been used as a proxy to understand current environmental modifications and alterations. We present some case studies from Mexico for the conservation of nature, and some examples of the relationship between geodiversity and biodiversity relationship for the conservation of natural resources.